Politics, money, and persuasion : democracy and opinion in Plato's Republic - Russon, John, 1960- (Bloomington, Indiana : Indiana University Press, 2021)
"In Politics, Money, and Persuasion, distinguished philosopher John Russon offers a new framework for interpreting Plato's The Republic. For Russon, Plato's work is about the distinctive nature of what it is to be a human being and, correspondingly, what is distinctive about the nature of human society. Russon focuses on the realities of our everyday experience to come to profoundly insightful assessments of our human realities: the nature of the city, the nature of knowledge, and the nature of human psychology. Russon's argument concentrates on the ambivalence of logos, which includes reflections on politics and philosophy and their place in human life, how humans have shaped the environment, our interactions with money, the economy, and taking account, and the pursuit of the good in social and political systems. Politics, Money, and Persuasion offers a deeply personal but also practical kind of philosophical reading of Plato's classic text. It emphasizes the tight connection between the life of city and the life of the soul, demonstrating both the crucial role that human cognitive excellence and psychological health play in political and social life"--
Cover -- Tilte Page -- Copyright -- Table of Contents -- Acknowledgments -- Note on Translations and Citations -- Introduction -- I. The Nature of Platonic Writing -- II. The Method of This Work -- III. The Argument -- A. Politics, Money, and Persuasion -- 1 The Problem of Abstraction -- I. The Polis and the Problem of the Guardians -- II. Expertise and Writing -- III. Money -- IV. Technē, Money, and the Commercial Polis -- 2 The Currencies of Power -- I. Timocracy -- II. Oligarchy -- III. Democracy -- B. The Vicissitudes of Opinion -- 3 True Opinion -- I. Socrates and the New Intellectuals -- II. Knowledge and the "Divided Line" -- III. Sophistry -- 4 Persuasion -- I. Persuasion -- II. Virtue -- III. Corruption -- Conclusion -- Bibliography -- Index of Subjects -- Index of Passages.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on August 25, 2021).
eBooks on EBSCOhost
Keywords: Plato -- Political and social views; Plato; Plato; Republic (Plato); Political science -- Philosophy; Democracy; PHILOSOPHY -- Movements -- Phenomenology; Democracy; Political and social views; Political science -- Philosophy